The appeal to emotions in the discourse of populist political actors from Spain, Italy, France and the United Kingdom on Twitter - Alonso-Muñoz, Laura; Casero-Ripollés, Andreu (Frontiers in Communication, 2023)
Western democracies live a populist impulse. In this context, the consolidation of digital technologies plays a key role due to their possibilities of efficiently spreading messages. This research examines the role that emotions play in the communication strategy on Twitter of populist actors from four European countries: Spain, Italy, France and the United Kingdom. The sample comprises the messages shared by four European political parties: Podemos, 5 Star Movement, National Front and UKIP and their respective leaders during the analysis period. In total, 9,128 messages are analyzed. The main findings show that fear, uncertainty or resentment are the emotions most frequently used by populist parties and leaders. Likewise, negative emotions have been observed in those messages whose primary actor is the political, economic and media classes, the European Union or immigration, while positive emotions, such as joy or pride, are associated with the figure of the leader and the party.